2020
DOI: 10.1021/acssynbio.0c00105
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Feedback Control of an Antithetic Molecular-Titration Motif in Escherichia coli Using Microfluidics

Abstract: We study both in silico and in vivo the real-time feedback control of a molecular titration motif that has been earmarked as a fundamental component of antithetic and multicellular feedback control schemes in E. coli. We show that an external feedback control strategy can successfully regulate the average fluorescence output of a bacterial cell population to a desired constant level in real-time. We also provide in silico evidence that the same strategy can be used to track a time-varying reference signal wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Once trained, Cheetah segmentation masks were generated and used to calculate the number of cells and average GFP fluorescence per cell (Figure B,C). These results were compared to similar analyses using segmentation masks generated by ChipSeg that we , and others , have previously implemented in a similar experimental setup (Supplementary Movie 1; Methods).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once trained, Cheetah segmentation masks were generated and used to calculate the number of cells and average GFP fluorescence per cell (Figure B,C). These results were compared to similar analyses using segmentation masks generated by ChipSeg that we , and others , have previously implemented in a similar experimental setup (Supplementary Movie 1; Methods).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Results from this experiment and related replica showed that the platform was able to accurately control average mCherry fluorescence in the cells for the duration of the experiment (Figures 3C, 3D; Supplementary Figure 1; Supplementary Movie 3). To evaluate the performance of the control experiment we measured the Integral Square Error (ISE) 41 for both controlled and uncontrolled chambers (i.e. those that received the same input in open loop).…”
Section: External Feedback Control Of Protein Expression In Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main approaches have been proven to be effective for the control of different processes (such as gene expression and cell proliferation), namely: i) open-or closed-loop controllers embedded into cells by means of synthetic gene networks [2][3][4][5][6]; ii) external controllers, where the controlled processes are within cells, while the controller (either at single cell or cell-population level) and the actuation functions are implemented externally via microfluidics-optogenetics/microscopy-flow cytometry platforms and adequate algorithms for online cell output quantification and control [7][8][9][10][11][12][13][14][15][16]; iii) multicellular control, where both the control and actuation functions are embedded into cellular consortia [17][18][19][20][21]. Plenty of examples of embedded controllers have been engineered across different cellular chassis; instead, applications of external and multicellular controllers in mammalian cells are scarce and either just theoretical or limited to proof of concepts.…”
Section: Introductionmentioning
confidence: 99%
“…The same core functions are implemented for both cell types, making the code flexible for other chassis and applications. The algorithm is easy to use and shows robust segmentation results in external feedback control experiments with microfluidics/microscopy platforms; ChipSeg can be easily adapted for open-loop experiments and other cell types/experimental settings.…”
Section: Introductionmentioning
confidence: 99%